Question

(3t^2−4s) ^2

Probability and combinatorics
ANSWERED
asked 2021-07-01
\(\displaystyle{\left({3}{t}^{{2}}−{4}{s}\right)}^{{2}}\)

Answers (1)

2021-07-02

We are given: \(\displaystyle{\left({3}{t}^{{2}}−{4}{s}\right)}^{{2}}\)
Use the rule: \(\displaystyle{\left({a}-{b}\right)}^{{2}}={a}^{{2}}-{2}{a}{b}+{b}^{{2}}\) where \(\displaystyle{a}={3}{t}^{{2}}\) and \(b=4s\)

\(=((3t^2)^2)-2(3t^2)(4s)+(4s)^2 =9t^4-24t^2\times s+16s^2\)

0
 
Best answer

expert advice

Have a similar question?
We can deal with it in 3 hours
...